Zoledronate promotes inflammatory cytokine expression in human CD14‐positive monocytes among peripheral mononuclear cells in the presence of γδ T cells. Issue 3 (23rd November 2020) - Takimoto, Reiko; Suzawa, Tetsuo; Yamada, Atsushi; Sasa, Kiyohito; Miyamoto, Yoichi; Yoshimura, Kentaro; Sasama, Yuji; Tanaka, Motohiro; Kinoshita, Mitsuhiro; Ikezaki, Kaori; Ichikawa, Makoto; Yamamoto, Matsuo; et al.
Summary: Bisphosphonates distributed to bone exert toxic effects specifically towards osteoclasts. On the other hand, intravenous administration of a nitrogen‐containing bisphosphonate (N‐BP) such as zoledronate induces acute‐phase reactions (APRs), including influenza‐like fever 1 day later, indicating an interaction with immunocompetent cells circulating blood. Although it has been reported that activation of γδ T cells is pivotal to induce an APR following treatment with zoledronate, downstream events, including the production of inflammatory cytokines after activation of γδ T cells, remain obscure. We investigated the effects of zoledronate on inflammatory cytokine expression in human peripheral blood mononuclear cells (PBMCs) in vitro. While zoledronate induced mRNA expressions of tumour necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, IL‐6 and interferon‐γ (IFN‐γ) in PBMC, depletion of γδ T cells abolished that zoledronate‐induced expression of those cytokines, indicating the necessity of γδ T cells for expression induction by zoledronate. However, which types of cells were responsible for the production of those cytokines in blood remained unclear. As it is generally accepted that monocytes and macrophages are primary sources of inflammatory cytokines, CD14 + cells from PBMC were exposed to zoledronate in the presence of PBMC, which resulted in induced expression of mRNAs for IL‐1β, IL‐6 and IFN‐γ, but not for TNF‐α. These results indicate that CD14 + cells are responsible, at least in part, for the production of IL‐1β, IL‐6 and IFN‐γ in blood exposed to zoledronate. This suggests that CD14 + cells play an essential role in the occurrence of APRs following N‐BP administration. Abstract : Intravenous administration of a nitrogen‐containing bisphosphonate such as zoledronate induces acute‐phase reactions (APRs), including influenza‐like fever 1 day later. While the activation of γδ T cells is essential for increased production of inflammatory cytokines required for induction of the APR, the types of cells that produce cytokines remained unclear. In this study, we found that CD14‐positive monocytes are responsible, at least in part, for the production of inflammatory cytokines after exposure of peripheral blood mononuclear cells to zoledronate.